Adequacy assessment of time of dispatch rules using fuzzy TOPSIS method - Alibeigi, A.; Asemi, A.; Munir, A.B.; Obaidellah, U.H. (2014)
Adequacy assessment of the existing Time of Dispatch (TD) rules is an academic primary step to improve the regulation of electronic commerce laws. This study aims to evaluate the ASEAN countries based on the adequacy of their TD rules. We propose an extended Fuzzy Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method for evaluation of ASEAN countries’ TD based on experts’ judgments. Fuzzy TOPSIS is initially a Multi Criteria Decision Making (MCDM) method. In this study, we extend it to a one criterion group decision making method. A group of academic experts is assigned for the judgment of the adequacy of TD in considering countries. The result shows that Singapore has the maximum adequacy in its TD rule among eight ASEAN countries.